THE ROLE OF INDEPENDENT LEARNING IN IMPROVING THE QUALITY OF EDUCATION - Rakhmatov Mahksud; Rasulova Maysara Nabiyevna (International Engineering Journal For Research & Development, 2021)
This article demonstrates the importance of independent education in improving the quality of education on the topic “Electricity generation” in the discipline “Use of electricity in the national economy” on the example of geothermal power plants and radioisotope sources of electricity.